Antibiotic resistance and virulence traits of bacterial pathogens from infected freshwater fish, Labeo rohita. (March 2018) - Ramesh, Dharmaraj; Souissi, Sami
Abstract: Bacterial infectious diseases are a main dangerous problem in Aquaculture farming. It causes multiple diseases in fish as well as in human being and it has considerable virulence potential. In this connection, the moot of study focus to discriminate bacterial isolates recovered from naturally diseased Labeo rohita fish and their virulent characteristics. Based on the β–haemolysis factor, four isolates (KADR11, KADR12, KADR13 and KADR14) were selected for further delineation. These bacterial isolates showed high similarity with Providencia rettgeri, Aeromonas sp., Aeromonas sp. and Aeromonas enteropelogenes respectively, using partial 16S r-RNA gene amplification and biochemical characterizations were also supported. The further study investigates the virulence characteristics of isolates showed separation of outer membrane proteins (OMPs) and lipopolysaccharides (LPS) which appeared between 19 _ 80 kDa and 20 _ 100 kDa in SDS _ PAGE analysis respectively. All the four strains were complete resistant (100%) to β-lactam antibiotics. L. rohita were injected intraperitoneally with 0 (control), 2.0 × 10 4, 2.0 × 10 5, 2.0 × 10 6, 2.0 × 10 7 and 2.0 × 10 8  cells/fish of Providencia rettgeri KADR11, Aeromonas sp. KADR12, Aeromonas sp. KADR13 and Aeromonas enteropelogenes KADR14 for the determination of lethal dose 50 (LD50 ) values, which were 2.4 × 10 7, 4.1 × 10 5, 2.7 × 10 7 and 7.4 × 10 5  cells/fish respectively. The results indicated that isolated strains were possessed the high pathogenic potential for L. rohita . Highlights: Antibiotic resistance and hemolytic activity of isolates were assessed. We report for the first time P. rettgeri in L. rohita. Aeromonas sp. KADR12 and A. enteropelogenes KADR14 isolates were considered to be highly virulent to host. Intraperitoneal injection of 2.0 × 10 8 Aeromonas sp. KADR12 and A. enteropelogenes KADR14 caused 100% mortality in L. rohita.